The outcomes of hypoglossal nerve stimulation in the management of OSA: A systematic review and meta-analysis - Anvesh R. Kompelli (KeAi Communications Co., Ltd., 2019)
Objectives: Obstructive sleep apnea (OSA) is a prevalent disease with significant health impacts. While first line therapy is CPAP, long-term compliance is low and device misuse is common, highlighting the need for alternative therapies. Upper airway surgery is one alternative, but substantial side effects hamper efficacy. A new alternative is an implantable hypoglossal nerve stimulator (HNS). These devices utilize neuromodulation to dilate/reinforce the airway and reduce side effects associated with traditional surgery. Several recent trials investigated the efficacy of these devices. The purpose of this study was to perform meta-analysis of available HNS studies investigating treatment of OSA to analyze objective and subjective outcomes and side effects. Methods: A comprehensive literature search of PubMed and Scopus was performed. Two independent reviewers examined clinical trials investigating HNS in treatment of sleep apnea in adults. Studies with objective and subjective endpoints in sleep were included for analysis. Adverse events from trials were also recorded. Results: Across 16 studies, 381 patients were analyzed. At 6 months (p = 0.008), mean SAQLI improved by 3.1 (95%CI, 2.6–3.7). At 12 months (p < 0.0001), mean AHI was reduced by 21.1 (95%CI, 16.9–25.3), mean ODI was reduced by 15.0 (95%CI, 12.7–17.4), mean ESS was reduced by 5.0 (95%CI, 4.2–5.8), mean FOSQ improved by 3.1 (95%CI, 2.6–3.4). Pain (6.2%:0.7–16.6), tongue abrasion (11.0%:1.2–28.7), and internal (3.0%:0.3–8.4)/external device (5.8%:0.3–17.4) malfunction were common adverse events. Conclusions: HNS is a safe and effective treatment for CPAP refractory OSA. Further study comparing HNS to other therapies is required. Keywords: Surgical treatment of obstructive sleep apnea, Sleep medicine, Obstructive sleep apnea